Pengaruh Sistem Kerja dan Stres Kerja terhadap Kinerja Perawat di RS Islam Sari Asih Arrahmah Tangerang - Siti Aminah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of work system and work-related stress on the performance of nurses at RS Islam Sari Asih Arrahmah Tangerang, considering that the nursing profession is highly vulnerable to physical and psychological pressure due to high workload and task complexity. The study employed a quantitative approach with an associative survey method, involving 65 nurses working in shift systems as respondents. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression. The results indicate that a proportional work system, clear task allocation, and regular shift schedules positively affect nurses’ performance, whereas workload imbalance, rapid shift rotations, high administrative demands, and ineffective communication increase work-related stress, which in turn reduces performance. Most respondents were categorized as experiencing moderate stress, yet they were still able to demonstrate good performance in terms of task accuracy, service quality, professionalism, and responsibility towards patients. These findings confirm that work-related stress serves as an important mediator in the relationship between work system and nurses’ performance. Practically, hospital management is advised to balance workload across shifts, enhance vertical and horizontal communication among staff, provide adequate managerial support and supervision, and implement stress management programs, professional development training, and fair work rotation. Such efforts are expected to create a healthy, safe, and productive work environment, improve nurse retention, and support the sustainable enhancement of healthcare service quality.